A Review on RFID Technology and Applications (International Journal of Engineering and Computer Science, 2018)
RFID is a stimulating, rapidly mounting, multidisciplinary technology, which is capable of automatically and exclusively identifying object or persons by radio frequency within certain proximity. RFID (Radio Frequency Identification) systems are emerging as one of the most persistent computing technologies in times past due to their low cost and their broad applicability. RFID systems distribution is hastily evolving and has the feasibility to affect various industries and applications. This paper primarily focuses on RFID technology with its hardware components, basic system and applications.